2016
DOI: 10.1097/md.0000000000004565
|View full text |Cite
|
Sign up to set email alerts
|

Smoking habits and benign prostatic hyperplasia

Abstract: Previous studies have warned against the promoting effects of cigarette smoking on benign prostatic hyperplasia (BPH). In contrast, some have argued that smoking confers a protective effect regarding BPH, while others have observed an aggravated effect. Thus, we performed this meta-analysis to determine whether cigarette use is associated with BPH risk.To identify articles from observational studies of relevance, a search was performed concurrent to March 21, 2016, on PubMed, Web of Science, Cochrane, EBSCO, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…That is, our present results cannot support the preventive effects of alcohol on BPH, and we could only conclude that the prevalence of BPH requiring treatment increases with ageing, although it is slightly less prevalent in all age groups if they drank alcohol. In the present study, the level of smoking was found to be significantly associated with the prevalence of BPH, which is in agreement with previous studies [27]. Although the level of smoking was significantly associated with a decreased prevalence of BPH in men aged <50 years, this finding might be secondary to the fact that a close relationship exists between smoking and alcohol consumption, and this topic requires further validation.…”
Section: Discussionsupporting
confidence: 93%
“…That is, our present results cannot support the preventive effects of alcohol on BPH, and we could only conclude that the prevalence of BPH requiring treatment increases with ageing, although it is slightly less prevalent in all age groups if they drank alcohol. In the present study, the level of smoking was found to be significantly associated with the prevalence of BPH, which is in agreement with previous studies [27]. Although the level of smoking was significantly associated with a decreased prevalence of BPH in men aged <50 years, this finding might be secondary to the fact that a close relationship exists between smoking and alcohol consumption, and this topic requires further validation.…”
Section: Discussionsupporting
confidence: 93%
“…However, a recent systematic review and meta-analysis based on 44,100 subjects showed no significant association between cigarette smoking and BPH risk for either ex-smokers or current smokers [46]. Another systematic review in 2017 showed marked associations of modest alcohol intake with decreased BPH diagnosis and lower urinary tract symptoms [46]. Hence, we can conclude that our results might not be substantially affected by the lack of data on smoking and alcohol consumption.…”
Section: Discussionmentioning
confidence: 57%
“…Neither smoking nor alcohol consumption status was included in our data, so we could not analyze their potential influences in this study. However, a recent systematic review and meta-analysis based on 44,100 subjects showed no significant association between cigarette smoking and BPH risk for either ex-smokers or current smokers [46]. Another systematic review in 2017 showed marked associations of modest alcohol intake with decreased BPH diagnosis and lower urinary tract symptoms [46].…”
Section: Discussionmentioning
confidence: 99%
“… 31 Moreover, a recent meta-analysis combining eight observational studies indicated there is no significant association between smoking and BPH risk either for ex-smokers or current smokers. 32 Although the NHIRD does not contain information regarding smoking habits of enrollees, a recent study by Cheng et al indicated that approximately 82.9% of patients with COPD are ever-smokers in Taiwan. 33 A public health report released by the Ministry of Health and Welfare of Taiwan indicated that the ratio of smokers in the male population of Taiwan was 44.3% in individuals aged 41–45 years, and 14.9% in individuals aged over 66 years.…”
Section: Discussionmentioning
confidence: 99%